PENGARUH RELATIONSHIP MARKETING, KOMUNIKASI PEMASARAN DAN CITRA PERUSAHAAN TERHADAP NIAT PERILAKU KONSUMEN MELALUI KEPUASAN PELANGGAN PADA VASA HOTEL SURABAYA - Chandra Kartika; Fauzi Hidayat; Efina Krinala (Universitas 17 Agustus 1945 Surabaya, 2019)
Effects of Relationship in Marketing, Marketing Communication, Corporate Image on the Intention of Consumer Behavior through Customer Satisfaction at Vasa Hotel Surabaya.This study aims to examine and analyze the effect of the relationship of marketing, marketing communication, corporate image on consumer behavior intentions through customer satisfaction at Vasa Hotel Surabaya. The number of respondents in this study was 130 people consisting of 68 men and 62 women. Analysis of this study uses Path Analysis. Data analysis was performed using statistics with SPSS tools. Based on the results of the overall data analysis, it can be seen that together the relationship relationship marketing, marketing communication, corporate image, customer satisfaction variables simultaneously have a significant influence on consumer behavior intentions.Keywords: Relationship marketing, marketing communication, trust icon corporate, customer satisfaction, consumer behavior intention